Analyzing the Effects of External Carotid Ligation and Preoperative Embolization of the Feeding Vessel to Prevent Postoperative Bleeding in Angiofibroma Excision - Allah Noor, Muhammad Mudassir, Saadat Ullah Khan, Shahibzada Fakhar Alam (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: This study evaluated the effectiveness of external carotid ligation and preoperative feeding vessel embolization to limit postoperative bleeding during angiofibroma excision. Methods: Eighty patients between 10 and 40 with angiofibroma excision at the Department of ENT, Hayatabad Medical Complex, Peshawar, between January 2020 and January 2022, were included in this Study. External carotid ligation (ECL) and preoperative feeding vascular embolization (EPV) were performed on these individuals. Following surgery, the patients were checked on at one week, one month, three months, six months, and one year. The patient's demographics, surgical conditions, side effects, and angiofibroma recurrence were recorded and examined. Results: The patient's average age was 21.3 ±7.6 years, and 100% were men. 79 of the 80 total cases were juvenile angiofibroma. The procedure lasted 65.2 minutes on average, while the average hospital stay was 1.3 days on average. There was a postoperative hemorrhage in 11 individuals (13.7%). It was found that there was no fatality rate. The incidence of postoperative bleeding in angiofibroma excision was shown to be significantly decreased (p=0.03) by preoperative Embolization with external carotid ligation. Conclusion: External carotid ligation and preoperative feeding vessel embolization may significantly decrease postoperative bleeding after angiofibroma excision. It was found that preoperative feeding vessel embolization before angiofibroma excision efficiently lowered the incidence of postoperative bleeding and should therefore be advised to patients for better treatment. Keywords: Angiofibroma excision, External carotid ligation, Preoperative Embolization, Postoperative bleeding.